The distribution of butterflies (Lepidoptera: Rhopalocera) in Haloze, East Slovenia - Rudi Verovnik (Natura Sloveniae)
Almost nothing has been known about the butterfly fauna of Haloze prior to our survey. During our field trips, including an extensive survey carried within the framework of the Student Research Camp Videm 2002, surprisingly high butterfly diversity was established. Altogether, 96 butterfly species were recorded at 67 studied sites. The highest butterfly diversity was registered in dry grasslands in the western part of the studied area. Due to the presence of rare and endangered species, such as Maculinea arion (Linne, 1758), Meleageria daphnis (Denis & Schiffermüller, 1775), and Polyommatus thersites (Cantener, 1825), these habitats would require more conservation efforts and a suitable management. The few remaining humid grasslands in the eastern part of the region still host the majority of specialized hygrophilous butterflies, including Maculinea nausithous (Bergsträsser, 1779), Maculinea teleius (Bergsträsser, 1779), and Lycaena dispar (Haworth, 1802). Some of these sites are proposed to be included into the Natura 2000 network, which could enable their suitable protection and management.